Pengembangan Mesin Pembuat Kawat Jala (Wire Mesh) Pada Bagian Pemotong Dan Penjalin Menggunakan Otomatisasi Berbasiskan Sistem Kontrol Arduino - Jayadi, Jayadi; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Wire mesh machine is a machine used to produce wire mesh or plaid wire mesh with various size of width, length and diameter used in various places such as sports field and as a fence for the beauty of the plant. This machine is equipped with the movement of wire cutting mechanism and also wire mesh for wire removal is not necessary, this machine is also equipped with electrical circuit as control system with arduino based program with function to control electric motor so that after woven wire can directly cut wire has been in woven according to the size set in the arduino program. From the results of testing this tool, there are still some shortcomings that result in the cutting and cutting process that occurred is still not perfect. This is caused by several factors that cause the failure during the process of cutting. And the test result or simulation which have been done on arduino program designed can be simulated as expected and control system applied by arduino microcontroller on this mesh wire machine goes well.Keywords : wire mesh machine, cutting wire, and wire mesh automatic.